Highly effective sequestration of Cd(Ⅱ) from aqueous solution using marine diatom biomass: Adsorption performances and mechanism - Wang, Xin; Wang, Jingfeng; Zhang, Shanfa; Li, Junguo (Frontiers in Environmental Science, 2023)
Highly efficient, economic feasible and environmentally friendly adsorbents have been a research hotspot for Cd(Ⅱ) sequestration. In this study, various nonliving marine diatom biomass were prepared for Cd(Ⅱ) removal. Results suggested that nonliving marine diatom biomass (Chaetoceros, Nitzschia, and Thalassiosira sp.) could efficiently remove Cd(II) from aqueous solution, with nonliving Nitzschia possessing the highest adsorption capacity. The adsorption capacity of nonliving Nitzschia was 289 – 430 mg g-1 (288 – 308 K) in the absence of ionic competition and under low turbidity conditions, which was much higher than that of most of adsorbents of great concern. The kinetic, isotherm and thermodynamic analysis suggested the adsorption of Cd(Ⅱ) was a spontaneous, endothermic and chemisorption involved process. Moreover, inorganic salts and turbidity showed negative effects on Cd(Ⅱ) adsorption, whereas humic acid showed a positive effect. Adsorption mechanism analysis demonstrated that amine and pyrrolic nitrogen groups were responsible for Cd(Ⅱ) adsorption. It is also worth noting that organics leaching during adsorption would also affect chemical bonds distribution on the biomass, which should be taken into account when elucidating the heavy metal adsorption mechanism of bio-adsorbents.